Korelasi Kandungan Antosianin Total dengan Parameter Warna (L*, a*, dan b*) dan Penanda Mikrosatelit pada Beras Hitam Lokal - Kristamtini, Kristamtini; Taryono, Taryono; Basunanda, Panjisakti; Murti, Rudi Hari (Jurnal Penelitian Pertanian Tanaman Pangan, 2017)
Black rice is a functional food for its  high anthocyanin contents expressed on purple-black rice color. The study aimed to determine the correlation between: total anthocyanin content with  L *, a *, and b * color variable, total anthocyanin content with color morphology and total anthocyanin content microsatellite markers. Eleven local black rice varieties  from Yogyakarta Assesment Institute of Agriculture Technology collections and two varieties of white rice (Situbagendit and Inpari 6 Jete) were planted on plastic pots in a green house. The tried was arranged   completely randomized design with five replications. At three weeks after planting, the leaf samples were are taken for DNA isolation and further PCR amplifications  using four microsatellite markers (RM 180, RM 220, RM 224 and RM 252). The black rice grain were observed based on color morphology using a Chromameter and analyzed  for then anthocyanin contents. Regression, correlation, and path analysis were conducted to determine the relationship between total anthocyanin content and L* a* b * color variable, color morphology, and microsatellite markers. The results showed that there is correlation between total anthocyanin content  with color parameters (L* = -0,568,  a* = -0,561, b*= 0,844).  Total anthocyanin content is correlation too with color scor of morfology and total   microsatellite markers ((RM 180 =-0,419, RM 220 =0,27, RM 224 =-0,493, RM 252 =0,265) and color scor of morphology  = -0,442. Selection of high-anthocyanin content of rice can use the color variable criterion (L*an  a* low, and  b * high). Microsatellite markers RM 220 and RM 252 can be used as moleculer markers for rice of high anthocyanin content.